HINDI GEETI - INTERACTION AND INNOVATION OF POETRY AND MUSIC: हिंदी गीति - काव्य और संगीत का पारस्परिक संबंध और नवाचार - Solanki, Pratibha (International Journal of Research -GRANTHAALAYAH, 2015)
Both music and literature are important means of expressing human emotions. With the coordination of both, the supernatural beauty is the creation of rain, which gives the human mind the realization of Sachchidananda and realization of Satyam-Shivam-Sundaram. According to the Varahapanishad, music is the perfect song, Bhagavata Purana refers to singing presented with dance and musical instruments and the goal of music is to provide pleasure. The same purpose is also for literature. Literature provides syllable Brahma and Shabda Brahma and music with Nadabrahm and Talbrahm. Both literature and music are closely related. Goddess Saraswati, the master of learning, has a veena in one hand and a book in the other. The policy of fraternity states संगीत और साहित्य दोनों ही मनुष्य के भावों को व्यक्त करने के महत्वपूर्ण माध्यम है। दोनों के समन्वय से अलौकिक सौंदर्य सृष्टि-वृष्टि होती है जो मानव मन को सच्चिदानंद की अनुभूति और सत्यम्-षिवम्-सुंदरम् की प्रतीति कराती है। वाराहोपनिषद के अनुसार संगीत सम्यक गीत है, भागवत पुराण नृत्य तथा वाद्य यंत्रों के साथ प्रस्तुत गायन को संगीत कहता है तथा संगीत का लक्ष्य आनंद प्रदान करना मानता है। यही उद्देष्य साहित्य का भी होता है। साहित्य अक्षर ब्रह्म और षब्द ब्रह्म से साक्षात कराता है तो संगीत नादब्रह्म और तालब्रह्म से। साहित्य और संगीत दोनों का साथ चोली-दामन का सा है। विद्या की अधिष्ठात्री देवी सरस्वती के एक हाथ में वीणा है तो दूसरे में पुस्तक भी है। भर्तृहरिकृत नीति-षतकम् में कहा गया है